2012
DOI: 10.1063/1.3682776
|View full text |Cite
|
Sign up to set email alerts
|

B80 and B101–103 clusters: Remarkable stability of the core-shell structures established by validated density functionals

Abstract: Prompted by the very recent claim that the volleyball-shaped B(80) fullerene [X. Wang, Phys. Rev. B 82, 153409 (2010)] is lower in energy than the B(80) buckyball [N. G. Szwacki, A. Sadrzadeh, and B. I. Yakobson, Phys. Rev. Lett. 98, 166804 (2007)] and core-shell structure [J. Zhao, L. Wang, F. Li, and Z. Chen, J. Phys. Chem. A 114, 9969 (2010)], and inspired by the most recent finding of another core-shell isomer as the lowest energy B(80) isomer [S. De, A. Willand, M. Amsler, P. Pochet, L. Genovese, and S. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
112
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 91 publications
4
112
0
Order By: Relevance
“…NICS values can be used as a measure of aromaticity, where negative value means aromaticity, and positive value shows antiaromaticity. Computed NICS values, shown in Table 1, reveals that all the most stable fullerene isomers B cage seems to have the largest negative NICS value -66.4 ppm with higher than any reported value for boron cages, including the core-shell structure B 101 , B 80 and B 38 cages reported in [13,31]. As an another stability measure, we compute HOMO-LUMO energy gap (E g ) [43][44][45] and they are given in Table 1.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…NICS values can be used as a measure of aromaticity, where negative value means aromaticity, and positive value shows antiaromaticity. Computed NICS values, shown in Table 1, reveals that all the most stable fullerene isomers B cage seems to have the largest negative NICS value -66.4 ppm with higher than any reported value for boron cages, including the core-shell structure B 101 , B 80 and B 38 cages reported in [13,31]. As an another stability measure, we compute HOMO-LUMO energy gap (E g ) [43][44][45] and they are given in Table 1.…”
mentioning
confidence: 95%
“…Relative stability analysis of 2D and 3D boron isomers reveal that PBE0 and TPSS functionals are more favorable over hybrid B3LYP [33,34]. Specifically, Li et al found that PBE, PBE0, TPSS and TPSSh basis sets are more reliable to describe the relative stabilities of B 80 isomers [31]. Hence, all the DFT computations were performed using the Gaussian 09 [35] quantum chemistry package and Perdew-Burke-Ernzerhof (PBE) [36] and Tao-Perdew-Staroverov-Scuseria (TPSS) [37] functionals were used throughout the study along with the 6-31G(d; p) basis set.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10] In the SA procedure, the system is first heated up to a high temperature (exceeding the melting point) and then gradually cooled down to room temperature via molecular dynamics (MD) or Monte Carlo simulations, which can be combined with either empirical potentials or first-principles methods. Even though SA procedure combined with first-principles calculations is a robust method and has been successfully employed to a series of clusters, such as Cd n Te n (n = 1-14), [11] Li n (n = 20,30,40,50), [12] P + 2m+1 (m = 1-12), [13] B 28 , [14] B 80 , [15] and B [101][102][103] , [16] it cannot guarantee the global minimum of the PES unless the annealing time is sufficiently long.…”
Section: Introductionmentioning
confidence: 99%